The Government's Adaptive Capacity in Developing Marine Tourism Potential in Makassar City - Andi Muhammad Rifqi Fathullah; Muhammad Irvan Nur Iva; Rahayu; Herman H. Dody (Public Service and Governance Journal, 2026)
This study aims to analyze the development of marine tourism in Makassar City. The city of Makassar has rich maritime potential with a combination of coastal areas and small islands that have underwater ecosystems and beautiful beach scenery, supporting the formation of marine tourism. Although there is regulatory support from various relevant national regulations and regional policies to support the development of marine tourism, the facilitation of this development still faces several challenges, including sectoral ego, poor coordination between institutions, and inadequate participation from the local community. This research was examined through the adaptive capacity theory by Emerson and Gerlak (2014), which includes structural arrangements, leadership, knowledge and learning, and resources, while the research method used was a qualitative method examined using descriptive analysis. The results of this study indicate that increasing adaptive capacity through joint efforts, participatory leadership, collective learning, and effective resource management is crucial in promoting sustainable marine tourism. In this regard, the implementation of marine tourism in Makassar City needs to be formulated as a tourism management system that adapts to social, economic, and ecological changes in order to achieve sustainable regional development through marine tourism.